Assessing the Knowledge of High School Leaders about conflict Solution Strategies in the Workplace from Teachers Aspect in Jeddah City - Alzubayd, Fatimuh Salih Barakat (Journal of Educational and Psychological Sciences, 2021)
The study aimed to assess the knowledge of school leaders in the secondary stage of conflict resolution strategies (appeasement, dominance, cooperation, conciliation, avoidance…) in the work environment from the teachers ’point of view, in Jeddah Governorate, and whether there are statistically significant differences in strategies for conflict resolution between leaders due to the qualification variables Scientific and years of experience. And that is in the first semester of the academic year (1440-1441). The study followed the methodology quantitative analytical description using the questionnaire as a tool for the study. The study sample consisted of 712 female teachers who were randomly chosen. The study results indicated that the leaders' knowledge of conflict resolution strategies in the work environment in Jeddah Governorate was average. The order of the strategies followed came from school leaders (conciliation, cooperation, appeasement, avoidance, dominance). no statistically significant differences at the level of significance (0.05) due to the impact of the educational qualification in all fields. The study has many recommendations, including: Working on setting up training courses for school leaders at all stages to train them on how to diagnose the conflict, learn its causes and ways to deal with it, and build positive working relationships between parameters, appropriate for conflict resolution.
Keywords: strategies; conflict resolution; work environment; Female leaders; secondary school; evaluation